2011
DOI: 10.1111/j.1468-3083.2011.04086.x
|View full text |Cite
|
Sign up to set email alerts
|

Split‐face study of melasma patients treated with non‐ablative fractionated photothermolysis (1540 nm)

Abstract: Non-ablative FP can be considered as a valuable treatment option with short-term improvement in terms of mild reduction and softening the edges of melasma in patients with skin types I/II, if prior topical therapies failed. Treatment of patients with skin types III+ should be critically questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
1
7
0
6
Order By: Relevance
“…An open clinical study on treatment of melasma in 25 Asian patients using fractional 1550 nm laser recommended judicious use of FPT for treating Asian skin because of its limited efficacy . Recently a split face study on 14 female patients with melasma treated with non‐ablative FPT (1540 nm) showed good results in skin types I and II but emphasized its critical evaluation in patients with darker skin complexions . A study analyzing histological and electron microscopic changes after fractional resurfacing suggested that the clinical improvement should not be interpreted as a cure for melasma …”
Section: Discussionmentioning
confidence: 98%
“…An open clinical study on treatment of melasma in 25 Asian patients using fractional 1550 nm laser recommended judicious use of FPT for treating Asian skin because of its limited efficacy . Recently a split face study on 14 female patients with melasma treated with non‐ablative FPT (1540 nm) showed good results in skin types I and II but emphasized its critical evaluation in patients with darker skin complexions . A study analyzing histological and electron microscopic changes after fractional resurfacing suggested that the clinical improvement should not be interpreted as a cure for melasma …”
Section: Discussionmentioning
confidence: 98%
“…Already after one treatment, improvement has been described for photodamaged skin, skin laxity, facial rhytides and acne scarring. Positive experiences in our own clinical trial using the non-ablative fractionated ErYAG-laser to treat melasma [21] motivated us to perform the present study. However, ablative fractionated CO 2 -laser (Quantel Excel O2) showed only little efficacy in this indication and was clearly less effective than the standard laser treatment with the QS ruby laser (Sinon).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 17% of patients suffered from worsening lesions because of PIH (skin types III and IV). The authors noticed that despite its lower side effects, NAFL requires prudence in darker skin types (III+) because of the PIH risk, and sessions should be performed, if any at all, with low densities [24] .…”
Section: Non-ablative Fractionated Lasersmentioning
confidence: 99%